Determining management factors in dairy farms in Carchi, Ecuador - Terán Rosero, G.; Cobo, R. (Cuban Journal of Agricultural Science, 2017)
This study has the objective of determining management variables that characterize dairy farms in Carchi province, Ecuador, through the study of production factors. Management variables were analyzed, which are infrastructure, equipment, biosafety and hygienic measures, use and quality of water, animal health andwelfare, milking and milk management in each dairy farm. This study was conducted with information from 212 in 394 dairy farms. An optimal scaling of considered qualitative variables was performed. Later, factors that characterize each dairy farm were discovered through the analysis of main components and, finally,the found groups are studied with the application of the analysis of clusters. Data for analysis were taken from the primary research in dairy farms from Universidad Politécnica Estatal del Carchi (UPEC). There were evidences to confirm that there are no good management practices in dairy farms of this province. This studyreached a multivariate characterization and demonstrated that the application of different statistical methods allows to establish the bases to improve the process of decision-making and management, for dairy farms and for provincial authorities.Key words: analysis of main components, analysis of clusters, dairy farms